MANAGEMENT OF ECOTOURISM IN GEORGIA - Maia Meladze (European Scientific Journal, ESJ, 2014)
For many developing countries tourism is one of the main sources of income, creating and generating much needed employment opportunities for socio-economic development. Within tourism is the new trend known as ecotourism whose main aim is to minimize the negative aspects of tourism on the host country. Ecotourism is sustainable tourism segment which includes relatively quiet natural landscapes of inspection including the protected areas. In the international tourism market typical tour operators are searching for new products, new countries in order to diversify their tourism packages. This is a strategy to keep clients on board as well as to attract new ones. According to ecotourism statistics, it was seen from the eighties a marked shift from mass tourism to ecotourism and more and more tourists were seeking environmentally relevant holiday destinations. The ecotourism statistics further shows that nature tourism has generated, it is believed, as much as seven percent of all international travel expenditure and they further reveal that this rate is increasing by about ten to thirty percent each year. Significant attention must be paid to current problems connected with deterioration of global environmental conditions, such as: climate change, violation of the ozone layer, demographic explosions, ecosystem changes and threat to biodiversity, weak energy condition, pollution, water scarcity, and loss and destruction of protected natural areas and changes in the natural processes in the biosphere. The solutions to these challenges lie in the management of ecotourism to fight this exploitation through protection, conservation and utilization of valuable resources.